Preparation method of high-purity silicon dioxide and high-purity quartz
By using a variety of ore and industrial solid waste as raw materials, combined with acid process and ammonium fluoride leaching process, high-purity silica and high-purity quartz sand were successfully prepared, which solved the problems of high production costs and resource shortage in the existing technology, and achieved stable supply of high-purity products and high-value utilization of industrial solid waste.
Patent Information
- Application Number
- CN202510015733.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing technology is difficult to effectively solve the problems of high-purity silica and high-purity quartz, which are high-quality production costs, complex process flow and shortage of resources, especially when meeting the demand for ultra-high-purity quartz in the high-tech field.
Various ore and industrial solid waste such as coal gangue, fly ash, aluminosilicate ore are used as raw materials, and purified through acid process and ammonium fluoride leaching process to achieve the preparation of high-purity silica and high-purity quartz. This method is not limited to high-purity quartz mineral raw materials, with a wide range of raw materials, a mild production process, and no new pollutants are produced.
The purity of high-purity silica and high-purity quartz sand is achieved by more than 99.9%, reducing production costs, overcoming the problems of high energy consumption and equipment costs in traditional processes, and achieving high-value utilization of industrial solid waste.
Smart Images

Figure CN119797380A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of comprehensive resource utilization, solid waste resource utilization and mineral material processing, and specifically relates to a method for preparing high-purity silicon dioxide and high-purity quartz. Background Art
[0002] High-purity silicon dioxide and high-purity quartz sand are important raw materials for the preparation of quartz glass, integrated circuit boards, semiconductor chips, fiber optic communications, polysilicon, single crystal silicon and optical instruments. They are irreplaceable key raw materials in the fields of new energy solar energy, fiber optic communications, information technology, lasers, semiconductors, aerospace, national defense and military.
[0003] Since high-purity quartz is mostly used in high-tech fields, the entry threshold is high and the requirements vary greatly. The industry has not yet formed a unified definition standard for high-purity quartz. At present, the purity of high-purity quartz is still mainly evaluated by the content of a limited number of metal impurity elements. Foreign countries divide it into ultra-pure (impurity content 0.1~1ug / g), ultra-high purity (impurity content 1~8ug / g, SiO 2 Content> 99.999%), high purity (impurity content 8~50ug / g, SiO 2 Content 99.995% ~ 99.999%), medium and high purity (impurity content 50 ~ 300ug / g, SiO 2 Content 99.97% ~ 99.995%), medium purity (impurity content 300 ~ 5000ug / g, SiO 2 Content 99.5% ~ 99.97%), low grade (impurity content 5000 ~ 10000ug / g, SiO 2 Content 99% ~ 99.5%). There is no unified national standard for high-purity quartz products in my country. Based on the research results of domestic scholars and the product standards of domestic high-purity quartz enterprises, SiO 2 The mass fraction is 99.9~99.999wt%, Fe 2 O 3 Quartz sand with a content of <10×10-6ug / g is called high-purity quartz, SiO 2 Quartz products with a mass fraction of 99.9991wt% or more are called ultra-high purity quartz.
[0004] The impurity content and occurrence state in quartz ore are important factors that limit the quality of quartz sand. At present, the world is facing a shortage of crystal raw materials and high-purity quartz ores, and people must find new raw materials to replace crystals for the production of high-purity silicon dioxide. Although my country has huge reserves of vein quartz, and the proven reserves of various types of natural quartz are about 10 billion tons, it has a resource quantity advantage, but there are difficult-to-overcome natural defects in quality, such as the widespread presence of fluid inclusions and mineral inclusions. These natural defects have become a bottleneck restricting the production of ultra-high purity quartz in my country. At present, it still cannot meet the market demand for ultra-high purity quartz in the country's high-tech industries and defense military enterprises.
[0005] There are many studies on the artificial synthesis of high-purity silica using gas phase method and sol-gel method, but they all have high energy consumption, high equipment cost investment, and require lengthy process flow, all of which lead to high production costs. 3 ) or silicon tetrachloride (SiCl 4 ) is used as raw material to obtain high-purity silicon dioxide through hydrogen and oxygen hydrolysis at 1200-1600℃. The high temperature conditions in the process lead to energy consumption and the corrosiveness of the raw materials lead to equipment investment, which makes the production cost high. In addition, chlorosilane (HSiCl 3 ) or silicon tetrachloride SiCl 4 The production of silica first requires the use of silicon dioxide as a raw material and a high temperature carbon thermal reduction at 1900 ° C to prepare metallic silicon. Then, metallic silicon is reacted with HCl gas to produce distillable chlorosilane. The impurities are removed by distilling chlorosilane to obtain chlorosilane and silicon tetrachloride SiCl of synthetic meteoric silica with high purity. 4 Raw materials, it can be seen that the synthesis process of fumed silica is complicated, and the energy consumption and equipment corrosion protection costs are high. The sol-gel method for preparing high-purity silica requires the use of organosilicon compound ethyl silicate as raw material, adding alcohol as a co-solvent, and the organosilicon raw material undergoes hydrolysis and polycondensation under the catalytic action of acid or alkali to form a silica sol, which is then aged to form a silica gel. The gel is washed and calcined to obtain a high-purity silica product. The synthesis of organosilicon compound raw materials in the sol-gel method still requires high-temperature carbon thermal reduction of silica resources to convert them into metallic silicon, and then synthesizes chlorosilanes through metallic silicon and HCl gas, and then further synthesizes organosilicon. The preparation of silica by precipitation is limited by a large amount of impurities in industrial water glass, and the quality indicators of the final silica product are often not high. Artificial synthesis of high-purity silica is difficult to guarantee a stable supply of high-purity silica and high-purity quartz in terms of production scale and product quality. Summary of the invention
[0006] In view of the deficiencies of the above technical problems, the present invention proposes a method for preparing high-purity silicon dioxide and high-purity quartz. It is not limited to the traditional high-purity quartz ore as raw material, the raw material source is wide, the raw material cost is low, the production process conditions are relatively mild and no new pollutants are generated in the process, and the high-value comprehensive resource utilization of various ores, tailings, industrial solid waste or industrial by-products can be achieved. The purity of the obtained high-purity silicon dioxide and high-purity quartz sand is above 99.9%, and the highest can be higher than 4N~6N, which can generate important economic value and environmental value, and has important practical significance.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing high-purity silicon dioxide and high-purity quartz, comprising the following steps:
[0008] (1) Selecting a mixture of one or more materials selected from coal gangue, fly ash, aluminosilicate ore, bauxite beneficiation tailings, beneficiation tailings containing aluminosilicate ore, and ores containing aluminosilicate phases, industrial solid wastes and by-products as raw materials;
[0009] (2) pre-treating the raw material; then treating the pre-treated raw material by an acid process, and separating the solid and liquid to obtain an acid leaching solution and an acid leaching residue;
[0010] (3) leaching the acid leaching residue obtained in step (2) with an ammonium fluoride solution, collecting ammonia generated during the leaching reaction for use in step (4), and separating the solid and liquid after the leaching reaction to obtain an ammonium fluorosilicate solution and leached residue;
[0011] (4) introducing ammonia gas into the ammonium fluorosilicate solution obtained in step (3) to react, and after the reaction is completed, solid-liquid separation is performed to obtain a solid phase and ammonium fluoride;
[0012] (5) recycling the ammonium fluoride produced in step (4) for use in the leaching process of step (3); purifying the solid phase produced in step (4) by acid leaching, and separating the solid and liquid after the leaching reaction is completed to obtain the acid leached solid phase and the leachate;
[0013] (6) The acid-leached solid phase in step (5) is purified by calcination to obtain high-purity silicon dioxide and / or calcined and crystallized to obtain high-purity quartz sand.
[0014] The present invention abandons the step of ammonium fluoride leaching, and the purity of the obtained silicon dioxide and quartz sand is lower than 95% and does not exceed 98% at most, which is difficult to achieve the purity of more than 99.9% in the present invention.
[0015] If ammonium fluoride is replaced by other fluorides in the present invention, on the one hand, it is difficult to achieve selectivity in the leaching process, resulting in the mixing of impurities, increasing the difficulty of impurity removal and production costs; on the other hand, the recycling of the ammonium fluoride reagent in the process cannot be achieved, which will increase the reagent cost in the production process.
[0016] As a preferred embodiment of the present invention, the pretreatment method is at least one of crushing and grinding, roasting activation, thermal activation, and mechanical activation. For raw materials with larger block sizes, crushing and grinding to a suitable fineness can be performed directly for subsequent acid process treatment for raw materials with suitable fineness. Roasting activation, thermal activation or mechanical activation can also be further selected for activation treatment to obtain pretreated raw materials. The purpose of pretreatment is to create suitable conditions for the subsequent acid leaching process.
[0017] As a preferred embodiment of the present invention, in the step (2), the acid process is direct acid leaching or water leaching after acidification roasting; the leaching agent used in the direct acid leaching is at least one of sulfuric acid, nitric acid and hydrochloric acid, and the volume concentration of the acid in the leaching agent is 5% to 90%; the leaching liquid-solid mass ratio is 2:1 to 6:1, the temperature of the acid process is 15 to 200°C, and the time of the acid process is 0.5 to 3.5h.
[0018] During water leaching after acidification roasting, the leaching agent in the acidification roasting is sulfuric acid, the leaching liquid-solid mass ratio is 4:1-0.1:1, the roasting temperature is 150-350°C, and the roasting time is 0.5-3.5h; after acidification roasting, water leaching is performed, the water leaching temperature is 15-150°C, the leaching liquid-solid ratio is 6:1-2:1, and the time is 0.5h-4h.
[0019] As a preferred embodiment of the present invention, the ammonium fluoride produced in step (4) is recycled back to the leaching step of step (3) for leaching reaction with the initial raw material.
[0020] As a preferred embodiment of the present invention, in step (3), the mass concentration of the ammonium fluoride solution is 10% to 80%; the liquid-solid mass ratio of the ammonium fluoride solution leaching is 2:1 to 16:1, the temperature is 15 to 100° C., and the time is 0.5 to 3 hours.
[0021] As a preferred embodiment of the present invention, in the step (4), ammonia gas is introduced into the ammonium fluorosilicate solution until the pH value of the solution is 6-10; the reaction temperature of the ammonia gas introduction is 10-100°C.
[0022] The ammonia in step (4) is the ammonia collected during the reaction in step (3) and / or newly added ammonia and / or ammonia water.
[0023] As a preferred embodiment of the present invention, in the step (5), the leaching agent used in the acid leaching purification is at least one of various inorganic acids and organic acids including sulfuric acid, nitric acid, hydrochloric acid, hydrofluoric acid, and oxalic acid. The acid leaching solution used can be a single acid or a combination of multiple acids in different proportions; the acid leaching can be a multi-stage leaching of a single acid, corresponding to 1 to 8 leaching stages, or a sequential multi-stage leaching of multiple different acids, corresponding to 1 to 8 leaching stages, then a multi-stage sequential leaching of multiple different acids, corresponding to 1 to 8 leaching stages, 1 to 8 leaching times, and finally a multi-stage leaching of multiple combined acids, corresponding to 1 to 8 leaching stages; the acid volume concentration of the leaching agent is 5% to 100%, the leaching reaction temperature is 20 to 200°C, the leaching liquid-solid mass ratio is 10:1 to 2:1, and the leaching time is 0.5 to 7h.
[0024] As a preferred embodiment of the present invention, in the step (6), the calcination temperature is 800 to 1600° C., and the calcination time is 0.5 to 5 hours.
[0025] As a preferred embodiment of the present invention, the acid-leached solid phase obtained in step (5) is high-purity silicon dioxide; the purity of the high-purity silicon dioxide and the high-purity quartz obtained in step (6) are both above 99.9%.
[0026] As a preferred embodiment of the present invention, in step (2), the valuable metals in the acid leaching solution can be recovered by conventional recovery methods in the art.
[0027] As a preferred embodiment of the present invention, in step (3), the leached residue can be used as a product or as an intermediate product to recover valuable components therein, depending on the chemical composition of the raw material.
[0028] As a preferred embodiment of the present invention, the leachate produced in step (5) is recycled back to the acid leaching step in step (2) or reused after further treatment, depending on the type of the leaching agent.
[0029] Principle of the present invention:
[0030] First, the raw materials are subjected to an acid process to extract metal elements such as aluminum oxide, which are transferred into the leaching solution and can be further separated and recovered. At the same time, the synthesis of the final product has the effect of improving the quality and reducing impurities. The activation of the chemical reaction performance of silicon oxide in the raw materials is conducive to improving the selectivity of silicon dioxide in the subsequent leaching process, and also creates conditions for the mild conditions required for the subsequent production process reaction. Therefore, in the subsequent ammonium fluoride leaching process, silicon dioxide with high chemical activity can react quickly with ammonium fluoride under relatively mild conditions, which is not available in other silicon dioxide allotropes. The mild reaction conditions ensure the high selectivity of the leaching process, low energy consumption, and low reagent cost investment. Secondly, the precipitation process of ammonium fluorosilicate obtained by leaching ammonium fluoride is also a favorable link for impurity removal. The impurities introduced during the precipitation process mainly cause the inclusion of impurities in the solution during the precipitation process. Whether from the physical phase of the impurities or the complexity of the impurities encapsulated in silicon dioxide, the difficulty of removing them will be much less than the impurities encapsulated in quartz ore. Therefore, the efficiency of impurity removal in the subsequent impurity removal process can be improved, the complexity and technical difficulty in the subsequent impurity removal process can be reduced, and ultimately it is manifested as increasing product purity and reducing impurity removal costs. Finally, the regeneration cycle of multiple leaching agents can be realized in this process, which is conducive to further reducing production costs.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The preparation method of the present invention is applicable to a wide range of raw materials, and is not limited by the problem of tight supply and high cost of high-purity quartz ore raw materials. It also overcomes the problems of lengthy production process and high production cost in the process of artificially synthesizing high-purity silicon dioxide.
[0033] (2) The present invention conducts acid leaching, ammonium fluoride leaching and acid leaching to improve the impurity removal rate, reduce the technical difficulty and the difficulty of leaching conditions, and achieve the effect that the purity of high-purity quartz sand is higher than 3N, and the highest can be higher than 4N~6N. In addition, the preparation method has low raw material cost, no new pollutants are generated during the production process, and the production cost is also low, which can realize the high-value comprehensive resource utilization of various industrial solid wastes. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of a method for preparing high-purity silicon dioxide and high-purity quartz. DETAILED DESCRIPTION
[0035] The present invention is not limited to the following embodiments, and various modifications and improvements can be made without departing from the spirit and scope of the present invention. For example, the electrolysis conditions can be adjusted and optimized according to actual conditions. In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0036] A method for preparing high-purity silicon dioxide and high-purity quartz comprises the following steps:
[0037] (1) A mixture of one or more materials selected from coal gangue, fly ash, various aluminum silicate ores, bauxite beneficiation tailings, various beneficiation tailings containing aluminum silicate ores, various ores containing aluminum silicate phases, industrial solid wastes and by-products is selected as the raw material.
[0038] (2) Pretreatment is performed according to the properties of the raw materials selected in step (1), and the pretreatment method is at least one of crushing and grinding, roasting, thermal activation, and mechanical activation. For raw materials with larger block sizes, crushing and grinding is performed to a suitable fineness. For raw materials with suitable fineness, subsequent acid process treatment can be directly performed, and roasting activation, thermal activation, or mechanical activation can be further selected for activation treatment to obtain pretreated raw materials, thereby creating suitable conditions for subsequent acid leaching process.
[0039] (3) The raw material pretreated in step (2) is treated by an acid process, wherein the acid process is direct acid leaching or water leaching after acidification and roasting, wherein the valuable metal elements such as aluminum oxide are extracted from the raw material by the acid process, and the solid-liquid separation is performed after the acid process to obtain an acid leaching solution and an acid leaching residue.
[0040] (4) Leaching the acid leaching residue obtained in step (3) with ammonium fluoride, collecting ammonia gas during the reaction for subsequent processes, and separating the solid and liquid after the leaching reaction to obtain an ammonium fluorosilicate solution and leaching residue. The acid leaching solution obtained in step (3) can be used to further separate and recover the valuable components therein.
[0041] (5) Ammonia gas is introduced into the ammonium fluorosilicate solution obtained in step (4) to perform a titration precipitation reaction, and after the reaction is completed, solid-liquid separation is performed to obtain a solid phase and ammonium fluoride. The leached residue obtained in step (4) can be used as a product or as an intermediate product to recover the valuable components therein according to the different chemical components in the raw materials.
[0042] (6) The ammonium fluoride produced in step (5) is recycled back to the leaching step of step (4) for leaching reaction with the initial raw material. The solid phase produced in step (5) is purified by acid leaching, and after the leaching reaction is completed, the solid and liquid are separated to obtain acid-leached solid phase high-purity silica and leachate.
[0043] (7) The acid leached solid phase in step (6) is calcined and purified to obtain high-purity quartz sand. The leaching solution produced in step (5) can be recycled to the acid leaching step in step (3) or reused after further treatment, depending on the type of leaching agent.
[0044] The acid process treatment conditions in step (3) of the present invention are that the leaching agent used in the direct acid leaching is one of sulfuric acid, nitric acid and hydrochloric acid, or a mixture of different acids; the volume concentration of the leaching solution acid is preferably 5% to 90%, more preferably 10% to 90%, and more preferably 20% to 90%; the leaching solution solid mass ratio is preferably 2:1 to 6:1, more preferably 3:1 to 6:1, and more preferably 3:1 to 5:1; the reaction temperature is preferably 15 to 200°C, more preferably 50 to 200°C, and more preferably 80 to 180°C; the reaction time is preferably 0.5 to 3.5h, more preferably 0.5 to 3h, and more preferably 1 to 2h.
[0045] The acidified roasting agent used in the water leaching after acidified roasting is sulfuric acid, and the mass ratio of roasted acid ore is preferably 4:1-0.1:1, more preferably 3:1-0.5:1, and more preferably 2:1-1:1; the roasting temperature is preferably 150-350°C, more preferably 150-300°C, and more preferably 150-250°C; the roasting time is 0.5-3.5h, more preferably 0.5-3h, and more preferably 1-2h; the water leaching temperature after roasting is preferably 15-150°C, more preferably 15-150°C, and more preferably 25-100°C; the leaching liquid-solid ratio is preferably 6:1-2:1, more preferably 3:1-6:1, and more preferably 3:1-5:1; the leaching time is preferably 0.5h-4h, more preferably 0.5-3h, and more preferably 1-2h. During the leaching reaction, the leaching liquid and the raw material are fully stirred to fully mix and contact.
[0046] The ammonium fluoride leaching reaction conditions in step (4) of the present invention are as follows: the leaching liquid preferably adopts an ammonium fluoride solution and a supersaturated ammonium fluoride solution, and more preferably a supersaturated ammonium fluoride solution; the mass concentration of ammonium fluoride is preferably controlled to be 10% to 80%, more preferably 40% to 80%, and more preferably 60% to 80%; the solid mass ratio of the leaching liquid is preferably 2:1 to 16:1, more preferably 4:1 to 16:1, and more preferably 8:1 to 16:1; the reaction temperature is preferably 15 to 100° C., more preferably 40 to 100° C., and more preferably 60 to 100° C.; the reaction time is preferably 0.5 to 3.5 h, more preferably 1 to 3.5 h, and more preferably 2 to 3.5 h; and the leaching reaction is carried out by sufficient stirring to ensure that the leaching liquid and the raw material are fully mixed and contacted.
[0047] The ammonia gas in step (5) of the present invention may be the ammonia gas collected during the reaction in step (4), or new ammonia gas or new ammonia water may be added.
[0048] The conditions for the titration precipitation reaction of introducing ammonia gas into the ammonium fluorosilicate solution in step (5) of the present invention are as follows: the reaction temperature is preferably 10 to 100° C., more preferably 40 to 100° C., and more preferably 60 to 100° C.; the pH of the titration endpoint solution is preferably 6 to 10, more preferably 6 to 9, and more preferably 7 to 9.
[0049] The acid used for acid leaching and purification in step (6) of the present invention is various inorganic acids and organic acids including sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid and oxalic acid. The acid leaching solution used can be a single acid or a combination of multiple acids in different proportions.
[0050] The acid leaching in step (6) of the present invention can be multi-stage leaching with one acid, or can be multi-stage leaching with multiple different acids in sequence, or multi-stage leaching with multiple different acids in sequence, or can be multi-stage leaching with multiple combined acids.
[0051] The reaction conditions of the acid leaching in step (6) of the present invention are as follows: the acid volume concentration is preferably 5% to 100%, more preferably 30% to 100%, and more preferably 40% to 80%; the leaching reaction temperature is preferably 20 to 200° C., more preferably 90 to 200° C., and more preferably 90 to 170° C.; the leaching liquid-to-solid mass ratio is preferably 10:1 to 2:1, more preferably 8:1 to 2:1, and more preferably 6:1 to 3:1; the leaching time is preferably 0.5 to 7h, more preferably 1 to 7h, and more preferably 2 to 7h; the number of leaching reaction stages is preferably 1 to 8 stages of countercurrent leaching, more preferably 1 to 5 stages of countercurrent leaching, and more preferably 2 to 5 stages of countercurrent leaching.
[0052] The calcination conditions in step (7) of the present invention are as follows: the calcination temperature is preferably 800-1600°C, more preferably 800-1500°C, and more preferably 800-1300°C; the calcination time is 0.5-5h, more preferably 0.5-3h, and more preferably 0.5-2h.
[0053] Example 1
[0054] like Figure 1 As shown, a method for preparing high-purity silicon dioxide and high-purity quartz, the specific steps are as follows:
[0055] (1) A titanium concentrate is used as raw material. The chemical composition of the titanium concentrate is: TiO 2 content 48.6%, TFe content 20.65%, SiO 2 Content 1.89%, Al 2 O 3The content is 1.36%, the MnO content is 0.95%, the CaO content is 0.053%, and the rest is other inevitable impurities, physically adsorbed water, crystal water, organic matter, etc. The valuable metal elements are extracted by acid leaching. The reaction conditions of acid leaching are: the selected leaching agent is sulfuric acid, the volume concentration of sulfuric acid in the leaching solution is 70%, the solid mass ratio of the leaching solution is 4:1, the reaction temperature is 170℃, and the reaction time is 2h. During the leaching reaction, the leaching solution and the raw material are fully stirred to mix and contact. After the acid leaching is completed, the solid-liquid separation is carried out to obtain the acid leaching solution and the acid leaching residue. The obtained acid leaching solution is used to produce titanium dioxide through the sulfuric acid titanium dioxide process.
[0056] (2) Leaching the acid leaching residue obtained in step (1) in an ammonium fluoride solution under mild conditions, wherein the leaching reaction conditions are: using a supersaturated ammonium fluoride solution with a concentration of 60%, a reaction temperature of 80° C., a liquid-to-solid mass ratio of 10:1, and a leaching reaction time of 2 h. During the reaction, ammonia is collected for subsequent processes. After the leaching reaction is completed, solid-liquid separation is performed by filtering to obtain an ammonium fluorosilicate solution and leached residue.
[0057] (3) Ammonia gas is introduced into the ammonium fluorosilicate solution obtained in step (2) to perform a titration precipitation reaction, the reaction temperature is 60° C., the pH value of the solution at the titration endpoint is 8.5, and after the reaction is completed, solid-liquid separation is performed to obtain a solid phase and ammonium fluoride. The titanium content in the leached slag obtained in step (2) is 51.2%, which meets the requirements of high-titanium slag, and can be used as high-titanium slag to further recycle the titanium therein.
[0058] (4) The ammonium fluoride produced in step (3) is recycled back to step (2) for leaching reaction.
[0059] (5) The solid phase obtained in step (3) is subjected to acid leaching, and the acid leaching conditions are: sulfuric acid is selected as the leaching agent, the acid volume concentration is 40%, the leaching reaction temperature is 100° C., the leaching liquid-solid mass ratio is 4:1, the leaching time is 2 h, the leaching reaction stage number is 3 stages of countercurrent leaching, and the acid leaching is purified to obtain high-purity silicon dioxide with a purity of 99.99%.
[0060] (6) The high-purity silicon dioxide in step (5) is calcined under the following conditions: calcination temperature of 1300° C. and calcination time of 2 h. After calcination and crystallization, 4N grade artificial synthetic high-purity quartz sand with a purity of 99.99% is obtained.
[0061] (7) The leachate produced in step (5) is recycled and used in step (1) for acid leaching of the raw material.
[0062] Example 2
[0063] like Figure 1 As shown, a method for preparing high-purity silicon dioxide and high-purity quartz, the specific steps are as follows:
[0064] (1) Taking coal gangue from Yunnan as raw material, the chemical composition and mass percentage of each component of the coal gangue sample are as follows: SiO 2 Content 42.73%; Al 2 O 3 Content 20.81%; Fe 2 O 3 content 12.28%; CaO content 1.61%; MgO content 2.01%; TiO 2 The content is 4.52%, and the rest is other inevitable impurities, physically adsorbed water, crystal water, organic matter, etc. The gangue is ground to a particle size of -0.074 mm, accounting for 90%, and then thermally activated at 600°C for 1h. The obtained raw material is leached with sulfuric acid, and the reaction conditions of the leaching are: the selected leaching agent is sulfuric acid, the volume concentration of sulfuric acid in the leaching solution is 60%, the solid mass ratio of the leaching solution is 4:1, the reaction temperature is 180°C, and the reaction time is preferably 2h. During the leaching reaction, the leaching solution and the raw material are fully stirred to fully mix and contact. After the acid leaching is completed, solid-liquid separation is performed to obtain the acid leaching solution and the acid leaching residue. The acid leaching solution is used to further recover the valuable metal elements therein.
[0065] (2) The acid leaching residue obtained in step (1) is directly leached in an ammonium fluoride solution under mild conditions. The leaching reaction conditions are: using a supersaturated ammonium fluoride solution with a concentration of 70%, a reaction temperature of 80° C., a liquid-to-solid mass ratio of 8:1, and a leaching reaction time of 2 h. During the reaction, ammonia is collected for subsequent processes. After the leaching reaction is completed, solid-liquid separation is performed by filtering to obtain an ammonium fluorosilicate solution and leached residue. The obtained leached residue can be used as white carbon black and an additive for paints.
[0066] (3) introducing ammonia gas into the ammonium fluorosilicate solution obtained in step (2) to carry out a titration precipitation reaction, the reaction temperature is 60° C., the pH value of the solution at the titration endpoint is 9, and after the reaction is completed, the solid-liquid separation is carried out to obtain a solid phase and ammonium fluoride, and the ammonium fluoride produced in step (3) is recycled to step (2) for leaching reaction.
[0067] (4) The solid phase obtained in step (3) is subjected to acid leaching, and the acid leaching conditions are as follows: the first stage leaching uses nitric acid as a leaching agent, the acid volume concentration is 20%, the leaching reaction temperature is 90° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 2 hours; the second stage leaching uses a mixed acid of hydrochloric acid and hydrofluoric acid as a leaching agent, the volume ratio of the two acids is 1:1, the acid volume concentration is 35%, the leaching reaction temperature is 90° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 1 hour; the third stage leaching uses sulfuric acid as a leaching agent, the acid volume concentration is 50%, the leaching reaction temperature is 110° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 2 hours; and the acid leaching is performed to purify and obtain high-purity silicon dioxide with a purity of 99.99%.
[0068] (5) The acid-leached solid phase high-purity silica in step (4) is calcined under the following conditions: calcination temperature of 800° C. and calcination time of 2 h. After calcination, 4N grade artificial synthetic high-purity silica with a purity of 99.99% is obtained.
[0069] (6) The leachate produced in step (4) is further treated to regenerate the acid therein and then recycled for use in the acid leaching process of step (4).
[0070] Example 3
[0071] like Figure 1 As shown, a method for preparing high-purity silicon dioxide and high-purity quartz, the specific steps are as follows:
[0072] (1) Using fly ash from Sichuan as raw material, the chemical composition of the fly ash sample is: SiO 2 Content 41.03%; Al 2 O 3 Content 39.12%; Fe 2 O 3 Content 2.13%; MgO content 0.32%; TiO 2 The content is 1.32%, and the balance is other inevitable impurities, physically adsorbed water, crystal water, organic matter, etc. Fly ash is leached by sulfuric acid, and the reaction conditions of the leaching are: the selected leaching agent is sulfuric acid, the volume concentration of sulfuric acid in the leaching solution is 50%, the leaching solution-solid mass ratio is 4:1, the reaction temperature is 15°C, and the reaction time is 3.5h. During the leaching reaction, the leaching solution and the raw material are fully stirred to fully mix and contact. After the acid leaching is completed, solid-liquid separation is performed to obtain the acid leaching solution and the acid leaching residue, and the acid leaching solution is used to further recover the valuable metal elements therein.
[0073] (2) The acid leaching residue obtained in step (1) is directly leached in an ammonium fluoride solution under mild conditions. The leaching reaction conditions are: using an 80% supersaturated ammonium fluoride solution, a reaction temperature of 70° C., a liquid-solid mass ratio of 8:1, and a leaching reaction time of 2 h. During the reaction, ammonia is collected for subsequent processes. After the leaching reaction is completed, solid-liquid separation is performed by filtering to obtain an ammonium fluorosilicate solution and leached residue, and the leached residue can be used as white carbon black.
[0074] (3) Ammonia gas is introduced into the ammonium fluorosilicate solution obtained in step (2) to perform a titration precipitation reaction, the reaction temperature is 80° C., the pH value of the solution at the titration endpoint is 8.5, and after the reaction is completed, the solid-liquid separation is performed to obtain a solid phase and ammonium fluoride. The generated ammonium fluoride is recycled back to step (2) for leaching reaction.
[0075] (4) The solid phase obtained in step (3) is subjected to acid leaching, and the acid leaching conditions are as follows: the first acid leaching uses nitric acid as a leaching agent, the acid volume concentration is 20%, the leaching reaction temperature is 90°C, the leaching liquid-solid mass ratio is 4:1, the leaching time is 2h, and the number of leaching sections is 2-stage countercurrent leaching; the second leaching uses hydrochloric acid as a leaching agent, the acid volume concentration is 35%, the leaching reaction temperature is 80°C, the leaching liquid-solid mass ratio is 4:1, the leaching time is 1h, and the number of leaching sections is 2-stage countercurrent leaching; the third leaching uses hydrofluoric acid as a leaching agent, the acid volume concentration is 10%, the leaching reaction temperature is 25°C, the leaching liquid-solid mass ratio is 4:1, and the leaching time is 2h; the fourth leaching uses sulfuric acid as a leaching agent, the acid volume concentration is 60%, the leaching reaction temperature is 120°C, the leaching liquid-solid mass ratio is 4:1, the leaching time is 2h, and the number of leaching sections is 3-stage countercurrent leaching. Acid leaching and purification yield high-purity silicon dioxide with a purity of 99.996%.
[0076] (5) The acid-leached solid phase high-purity silica in step (4) is calcined under the following conditions: calcination temperature of 1200° C. and calcination time of 2 h. After calcination, 4N grade artificial synthetic high-purity quartz with a purity of 99.996% is obtained.
[0077] (6) The leachate produced in step (4) is further processed and reused.
[0078] Example 4
[0079] like Figure 1 As shown, a method for preparing high-purity silicon dioxide and high-purity quartz, the specific steps are as follows:
[0080] (1) Taking coal gangue from Yunnan as raw material, the chemical composition and mass percentage of each component of the coal gangue sample are as follows: SiO 2 Content 42.73%; Al 2 O 3 Content 20.81%; Fe 2 O 3 content 12.28%; CaO content 1.61%; MgO content 2.01%; TiO 2The content is 4.52%, and the rest is other inevitable impurities, physically adsorbed water, crystal water, organic matter, etc. The gangue is ground to a particle size of -0.074 mm, accounting for 90%, and then thermally activated at 600°C for 1h. The obtained raw material is leached by sulfation roasting. The reaction conditions of sulfation roasting are: the selected roasting agent is sulfuric acid, the acid-ore mass ratio is 1:1, the acidification roasting temperature is 200°C, and the roasting time is 2h. The reaction conditions of water leaching after roasting are: the leaching liquid-solid mass ratio is 6:1, the reaction temperature is 15°C, and the reaction time is preferably 2h. During the leaching reaction, the leaching liquid and the raw material are fully stirred to fully mix and contact. After the acid leaching is completed, the solid-liquid separation is performed to obtain the acid leaching liquid and the acid leaching residue. The acid leaching liquid is used to further recover the valuable metal elements therein.
[0081] (2) The acid leaching residue obtained in step (1) is directly leached in an ammonium fluoride solution under mild conditions. The leaching reaction conditions are: using an ammonium fluoride solution with a concentration of 10%, a reaction temperature of 15° C., a liquid-to-solid mass ratio of 2:1, and a leaching reaction time of 3 hours. During the reaction, ammonia is collected for subsequent processes. After the leaching reaction is completed, solid-liquid separation is performed by filtering to obtain an ammonium fluorosilicate solution and leached residue. The obtained leached residue can be used as white carbon black and an additive for paints.
[0082] (3) introducing ammonia gas into the ammonium fluorosilicate solution obtained in step (2) to carry out a titration precipitation reaction, the reaction temperature is 10° C., the pH value of the solution at the titration endpoint is 6, and after the reaction is completed, the solid-liquid separation is carried out to obtain a solid phase and ammonium fluoride, and the ammonium fluoride produced in step (3) is recycled to step (2) for leaching reaction.
[0083] (4) The solid phase obtained in step (3) is subjected to acid leaching, and the acid leaching conditions are as follows: the first stage leaching uses nitric acid as a leaching agent, the acid volume concentration is 100%, the leaching reaction temperature is 50° C., the leaching liquid-solid mass ratio is 10:1, and the leaching time is 0.5 h; the second stage leaching uses a mixed acid of hydrochloric acid and hydrofluoric acid as a leaching agent, the volume ratio of the two acids is 1:1, the acid volume concentration is 35%, the leaching reaction temperature is 90° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 1 h; the third stage leaching uses sulfuric acid as a leaching agent, the acid volume concentration is 50%, the leaching reaction temperature is 110° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 2 h; and the acid leaching is performed to purify the high-purity silicon dioxide with a purity of 99.992%.
[0084] (5) The acid-leached solid phase high-purity silica in step (4) is calcined to remove impurities and crystallize, and the calcination conditions are: calcination temperature 1600° C., calcination time 0.5 h, and after calcination, 4N grade artificial synthetic high-purity quartz sand with a purity of 99.995% is obtained.
[0085] (6) The leachate produced in step (4) is further processed and reused.
[0086] Example 5
[0087] like Figure 1 As shown, a method for preparing high-purity silicon dioxide and high-purity quartz, the specific steps are as follows:
[0088] (1) Taking coal gangue from Yunnan as raw material, the chemical composition and mass percentage of each component of the coal gangue sample are as follows: SiO 2 Content 42.73%; Al 2 O 3 Content 20.81%; Fe 2 O 3 content 12.28%; CaO content 1.61%; MgO content 2.01%; TiO 2 The content is 4.52%, and the rest is other inevitable impurities, physically adsorbed water, crystal water, organic matter, etc. The gangue is ground to a particle size of -0.074 mm, accounting for 90%, and then thermally activated at 600°C for 1h. The obtained raw material is leached with sulfuric acid, and the reaction conditions of the leaching are: the selected leaching agent is sulfuric acid, the volume concentration of sulfuric acid in the leaching solution is 90%, the solid mass ratio of the leaching solution is 2:1, the reaction temperature is 200°C, and the reaction time is preferably 0.5h. During the leaching reaction, the leaching solution and the raw material are fully stirred to fully mix and contact. After the acid leaching is completed, the solid-liquid separation is carried out to obtain the acid leaching solution and the acid leaching residue. The acid leaching solution is used to further recover the valuable metal elements therein.
[0089] (2) The acid leaching residue obtained in step (1) is directly leached in an ammonium fluoride solution under mild conditions. The leaching reaction conditions are: using an ammonium fluoride solution with a concentration of 50%, a reaction temperature of 100° C., a liquid-solid mass ratio of 16:1, and a leaching reaction time of 3 hours. During the reaction, ammonia is collected for subsequent processes. After the leaching reaction is completed, solid-liquid separation is performed by filtering to obtain an ammonium fluorosilicate solution and leached residue. The leached residue obtained can be used as white carbon black and an additive for paints.
[0090] (3) introducing ammonia gas into the ammonium fluorosilicate solution obtained in step (2) to carry out a titration precipitation reaction, the reaction temperature is 100° C., the pH value of the solution at the titration endpoint is 10, and after the reaction is completed, the solid-liquid separation is carried out to obtain a solid phase and ammonium fluoride, and the ammonium fluoride produced in step (3) is recycled to step (2) for leaching reaction.
[0091] (4) The solid phase obtained in step (3) is subjected to acid leaching, and the acid leaching conditions are as follows: the first stage leaching uses nitric acid as a leaching agent, the acid volume concentration is 5%, the leaching reaction temperature is 200° C., the leaching liquid-solid mass ratio is 2:1, and the leaching time is 7 hours; the second stage leaching uses a mixed acid of hydrochloric acid and hydrofluoric acid as a leaching agent, the volume ratio of the two acids is 1:1, the acid volume concentration is 35%, the leaching reaction temperature is 90° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 1 hour; the third stage leaching uses sulfuric acid as a leaching agent, the acid volume concentration is 50%, the leaching reaction temperature is 110° C., the leaching liquid-solid mass ratio is 4:1, and the leaching time is 2 hours; and the acid leaching is performed to purify the high-purity silicon dioxide with a purity of 99.95%.
[0092] (5) The acid-leached solid phase high-purity silica in step (4) is calcined under the following conditions: calcination temperature of 1000° C. and calcination time of 5 h. After calcination, 3N grade artificial synthetic high-purity silica with a purity of 99.98% is obtained.
[0093] (6) The leachate produced in step (4) is further processed and reused.
[0094] Comparative Example 1
[0095] The only difference between the method for preparing high-purity silicon dioxide and high-purity quartz described in this comparative example and Example 1 is that the ammonium fluoride solution is replaced by ammonium sulfate solution. The purity of the obtained high-purity silicon dioxide is 65.5%, and the purity of the quartz is 76.2%.
[0096] The above is the entire content of the present invention. Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing high-purity silicon dioxide and high-purity quartz, characterized in that: The steps include: (1) Selecting a mixture of one or more materials selected from coal gangue, fly ash, aluminosilicate ore, bauxite beneficiation tailings, beneficiation tailings containing aluminosilicate ore, and ores containing aluminosilicate phases, industrial solid wastes and by-products as raw materials; (2) pre-treating the raw material; then treating the pre-treated raw material by an acid process, and separating the solid and liquid to obtain an acid leaching solution and an acid leaching residue; (3) leaching the acid leaching residue obtained in step (2) with an ammonium fluoride solution, collecting ammonia generated during the leaching reaction for use in step (4), and separating the solid and liquid after the leaching reaction to obtain an ammonium fluorosilicate solution and leached residue; (4) introducing ammonia gas into the ammonium fluorosilicate solution obtained in step (3) to react, and after the reaction is completed, solid-liquid separation is performed to obtain a solid phase and ammonium fluoride; (5) recycling the ammonium fluoride produced in step (4) for use in the leaching process of step (3); purifying the solid phase produced in step (4) by acid leaching, and separating the solid and liquid after the leaching reaction is completed to obtain the acid leached solid phase and the leachate; (6) The acid-leached solid phase in step (5) is purified by calcination to obtain high-purity silicon dioxide and / or calcined and crystallized to obtain high-purity quartz sand.
2. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: The pretreatment method is at least one of crushing and grinding, roasting activation, thermal activation, and mechanical activation.
3. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: In the step (2), the acid process is direct acid leaching or water leaching after acidification and roasting; The leaching agent used in the direct acid leaching treatment is at least one of sulfuric acid, nitric acid and hydrochloric acid, and the volume concentration of the acid in the leaching agent is 5% to 90%; the leaching liquid-solid mass ratio is 2:1 to 6:1, the temperature is 15 to 200°C, and the time is 0.5 to 3.5 hours; During water leaching after acidification roasting, the leaching agent in the acidification roasting is sulfuric acid, the leaching liquid-solid mass ratio is 4:1-0.1:1, the roasting temperature is 150-350°C, and the roasting time is 0.5-3.5h; after acidification roasting, water leaching is performed, the water leaching temperature is 15-150°C, the leaching liquid-solid ratio is 6:1-2:1, and the time is 0.5h-4h.
4. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: In the step (3), the mass concentration of the ammonium fluoride solution is 10% to 80%; the liquid-to-solid mass ratio of the ammonium fluoride solution during leaching is 2:1 to 16:1, the temperature is 15 to 100° C., and the time is 0.5 to 3 hours.
5. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: In the step (4), ammonia gas is introduced into the ammonium fluorosilicate solution until the pH value of the solution is 6-10; the reaction temperature of the ammonia gas introduction is 10-100°C.
6. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: In the step (5), the leaching agent used in the acid leaching is an inorganic acid and / or an organic acid, the acid volume concentration of the leaching agent is 5% to 100%, the leaching reaction temperature is 20 to 200° C., the leaching liquid-solid mass ratio is 10:1 to 2:1, the leaching time is 0.5 to 7 hours, and the number of leaching stages is 1 to 8 stages.
7. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: In the step (6), the calcination temperature is 800 to 1600° C., and the calcination time is 0.5 to 5 hours.
8. The method for preparing high-purity silicon dioxide and high-purity quartz according to claim 1, characterized in that: The acid-leached solid phase obtained in step (5) is high-purity silicon dioxide; the purity of the high-purity silicon dioxide and the high-purity quartz obtained in step (6) are both above 99.9%.
Citation Information
Patent Citations
Comprehensive extraction method of ferro-silico-aluminum in gangue
CN102515279A
Method for producing white carbon black with coal gangue
CN102701222A
Preparation method of high-purity silicon dioxide
CN102874821A
Method for preparing silicon / aluminium series product by taking gangue as raw material
CN104743560A
Method for preparing white carbon black with polyaluminum ferric sulfate as byproduct from fly ash
CN104843716A